Information Ergonomics A theoretical approach and practical experience in transportation - Stein, Michael; Sandl, Peter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The variety and increasing availability of hypermedia information systems, which are used in stationary applications like operators$1 (Bconsoles as well as mobile systems, e.g. driver information and navigation systems in automobiles form a foundation for the mediatization of the society. From the human engineering point of view this development and the ensuing increased importance of information systems for economic and private needs require careful deliberation of the derivation and application of ergonomics methods particularly in the field of information systems. This book consists of two closely intertwined parts. The first, theoretical part defines the concept of an information system, followed by an explanation of action regulation as well as cognitive theories to describe man information system interaction. A comprehensive description of information ergonomics concludes the theoretical approach. In the second, practically oriented part of this book authors from industry as well as from academic institutes illustrate the variety of current information systems taken from different fields of transportation, i.e. aviation, automotive, and railroad. The reader thus gains an overview of various applications and their context of use as well as similarities and differences in design. This does not only include a description of the different information systems but also places them in the context of the theories and models, which were presented in the first part of this book.s
The Field of Information Systems -- Information Ergonomics -- Human aspect of information ergonomics -- Conflict between Ergonomic and Design -- Information Systems in Transport today -- Potential of Information Systems.
Keywords: Engineering; Computer science; Engineering design; Engineering; Engineering Design; Media Design; Industrial and Organisational Psychology; Innovation/Technology Management; Automotive Engineering